(untitled) (Revista Contexto & Educação, 2022)
This article aims to analyze the origin and specificities of the debate between teaching thinking or teaching how to do school based on a study carried out using theoretical and bibliographic sources of the epistemological ways of building the precepts of teaching to do and teaching think. Methodologically, the construction of the analysis of this article follows three sequenced paths, to analyze the historical formation of the meaning given when teaching to do as a synonym of rationality; the criticism of this precept and the challenge of teaching thinking for the construction of autonomy, establishing a theoretical dialogue with Edgar Morin (2019; 1973; 1996; 2003) and Paulo Freire (9997; 1995; 1990). It is concluded that this debate about the role of the school does not originate within the school itself, but in the social and political sphere from a historical construction involving the process of the epistemological origin of modern rationality. The school has a social commitment, historically built, to teach the rational being associated with the roots of modernity and capitalist relations of production. Thus, the knowledge that the school uses as a means and as an end in itself is associated with its practical usefulness, which makes the teaching practice of teaching to think difficult.